PENGEMBANGAN KEMAMPUAN BAHASA MELALUI BERCERITA GAMBAR HURUF HIJAIYYAH PAUD PAS ASSAKIINAH DI SAMBIREJO-MANTINGAN TAHUN AJARAN 2020/2021 - Sanusi, Gucik; Suwarno, Suwarno (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2021)
Development of Children's Language Skills Through Storytelling Method Hijaiyyah Letters PAUD PAS Assakiinah In Sambirejo Academic Year 2020/2021. In order to improve the development of children's language skills using the Hijaiyyah storytelling method, the aspects of children's development will not be missed in the formation of students' language to become better and students better understand capturing language using the Hijaiyyah letter image method easily. This is in accordance with the situation of PAUD PAS Assakiinah which uses a method to improve children's language, therefore the study conducted a qualitative descriptive study and used observation, interview and document methods. To reveal how the actual role process of learning aspects of developing children's language skills through the hijaiyyah storytelling method is, the authors formulate the following problems: (1) How are the children's language skills in PAUD Pas Assakiinah? (2) How is the ability to tell pictures of hujaiyyah letters in PAUD Pas Assakiinah? (3) How is the development of children's language skills through storytelling and pictures of Hijaiyyah letters in PAUD Pas Assakiinah? The conclusion drawn from the results of the study is the development of children's language skills through the method of telling stories with hijaiyyah letters at PASS Assakinah PAUD (a) developing good children's language (b) methods of telling stories with interesting hijaiyyah letters in accordance with the language of early childhood in PASS Assakinah PAUD.